Using soil phosphorus sorption saturation with Mehlich 3 extractant as a predictor for estimating risk of phosphorus losses by leaching from arable land - Jurga, Beata; Lipiński, Wojciech (Polish Journal of Agronomy, 2021)
Phosphorus (P) is essential for plant growth and yield. Balanced fertilization can produce a yield-sustaining effect, but excessive P applied to agricultural soils poses a risk by losing excess of phosphorus to the aquatic environment. This is undesir- able from both an economic and environmental perspective as it wastes a finite phosphorus rock and represents a serious environ- mental hazard in the form of pollution and eutrophication of the aquatic resources. For this reason, proven methods of estimating the risk of P losses from agricultural land are needed. The aim of this study was to assess the content of soil available phosphorus (SP) and soil phosphorus sorption saturation (Psat) in arable soils and assess if they can be used to predict P in waters from drain- age outlets from adjacent arable land. The determination of phos- phorus content in the soil and determination of Psat was carried out using Mehlich 3 extractant. Psat was calculated as the molar ratio of P to the extractable Fe and Al in one solution. The aver- age phosphorus content determined in the soil by the Mehlich 3 method was 101.8 mg kg-1. Psat was on average 11.8%. The aver- age content of phosphorus in water samples from drain outlets was 0.1 mgP dm -3.